Rationality as a Social Construction: What Does Individual Behavior Have To Say About Development in an Amazon Community? - Gramajo, Andrés Marroquín (Journal of Economic Issues (Association for Evolutionary Economics), 2008)
This article argues that two different manifestations of rational behavior can coexist and collide in a relatively homogeneous society. In the Ticuna community of Arara in the Colombian Amazon; on the one hand, the majority of villagers tend to reach relatively lower levels of material wealth, following Polanyi's idea of the pre-modern man (1968a; 1968b; 1968c), and also Sahlins' (1972) idea of the original affluent man. On the other hand, community leaders and schoolteachers tend to accumulate material wealth, following Polanyi's idea of modern-man (1968a; 1968b). These behavioral frameworks help explain the limited success of certain types of development programs in the Ticuna community.
Economics
Keywords: Amazon River Region; Colombia; Tucuna (South American people); behavioral economics; communication in economic development; economic development; economic policy; economics - moral & ethical aspects; pre-modern man; rationality; reason; saving and investment; statics & dynamics (social sciences); wealth